SENYAWA FLAVONOID DARI EKSTRAK ETIL ASETAT KULIT BATANG TUMBUHAN Bauhinia hullettii Prain DAN UJI IN VITRO SEL MURINE LEUKEMIA P-388 - Feri Ari Bangun Siahaan; Johni Azmi; Lenny Anwar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Isolation, characterization, and in vitro testing against murine leukemia P-388 cell of flavonoid compounds from Bauhinia hullettii Prain stem bark have beenperformed. Isolation was carried out by extraction and fractionation. Extraction usedmeceration method at room temperature to obtain n-Heksana extract, dicloromethaneextract, and etil acetate extract. Based on phytochemical testing, etil acetate extractcontain flavonoid compounds. Extraxct etil acetate was fractionated by vacumcolumn chromatography, gravitation column chromatography, and flash columnchromatography. The fractionation resulted yellow crystal that having melting pointof 188oC - 189oC. The in vitro testing against murine leukimia P-388 cell of isolatedflavonoid compounds show “medium” activity with IC50 = 22,5 μg/ml.Key word : Bauhinia hullettii Prain, Flavonoid, Murine Leukemia P-388 Cell